O sujeito reconstruído: sobre algumas imagens mallarmaicas na obra de Alejandra Pizarnik - Sérgio Bento (Estudos de Literatura Brasileira Contemporânea)
The analysis of Alejandra Pizarnik ́s poetry displays (to an attentive reader) a tangle of images that refer to one of the icons of Modern Poetry, the french writer Stéphane Mallarmé. However, it is noted, simultaneously, an extreme shift in the behavior of the poetic subject of the Argentinian writer, who - instead of vanishing in the self-referent significant theater - as in Mallarmé ́s -, gets in fl ated and turns the external world into her extension. What this article defends is that such action happens as a feedback to the weakening and fragmentation processes that afflict the so-called contemporary self.